SISTEM KOMPUTERISASI ADMINISTRASI SURAT DI REKTORAT UNIVERSITAS SAHID SURAKARTA - Cholil Jamhari; Dwi Retnoningsih; Sri Huning Anwariningsih (JURNAL GAUNG INFORMATIKA, 2017)
The system computerized administration of the letter in Rektorat University Sahid of Surakarta is enough but still need development, because the administration of the letter, still are spring computerized, the most of the data is not well, so difficult when ded the process of the search data. In addition the officer also difficulties when entering the number of letter, because the number of put in manual. Based on the problem is the author build the system computerized administration of the letter as a solution problems.The purpose of this thesis is build system computerized adminstration of letter in Rektorat University Sahid of Surakarta. This system is design using a method program and object oriented programming in use the language of the program PHP an d HTML5. The system computerized administration of the letter is expected to help and facilitate the perfome of employees become more effective and efficient in managing the administration of the letter. Testing system using the black box testing. The result of all testing is software built in the funcitional can serve as well and not found the mistakes syntax meaning.